The role of women in conflict resolution: the case of Yemen - Domingues, Elisabete Júlio (2020)
International media, non-governmental organizations and, the United Nations, among other actors, claim that Yemen is experiencing the worst humanitarian crisis ever. Amnesty International says that conflict is almost always followed by suffering and misery. Yemen is one of the countries most affected by conflict worldwide. In general, conflicts affect the entire population in different ways, however, they disproportionately affect women and children, who constitute the most vulnerable part of the population. Although there are studies that demonstrate that peace is more sustainable when women participate in peace-building processes, the truth is that they have not taken an active role in this area and have been constantly relegated to the background. This study aims to address the role played by women in conflict resolution to find out whether their involvement is a key factor in resolving the international conflict in Yemen.